The calf - Shaheen, safdar (Children publications; Karachi, 2008)
"The Calf by Quran Stories for Children" is a retelling of the story from the Quran, focusing on the incident of the golden calf, teaching young readers valuable lessons about faith, obedience, and the consequences of idolatry.